1991
DOI: 10.1016/0014-5793(91)81212-q
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the polyadenylation consensus sequence context in the genes of nuclear encoded mitochondrial proteins

Abstract: A compilation of the pre-mRNA ends of the genes of nuclear encoded mitochondrial proteins resulted in a consensus sequence of the type (T/A)NTTNNNNNTTTNAATAAA. Nucleotide positions +8, +13. +14, +16 and +17 downstream of the AATAAA sequence show also a predominance of nucleotide T. This consensus sequence suggests the importance of the immediate surroundings of the cannonical polyadenylation signal sequence AATAAA on the efficiency of" the cleavage and polyadenylation of this specific group of pre-mRNAs.Nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 107 publications
1
6
0
Order By: Relevance
“…The amino acid composition of the first 53 amino acids in the predicted hsp78 sequence is consistent with the properties of known mitochondrial leader peptides (46). Two TATA boxlike sequences are present at positions -103 and -93 in the 5' upstream sequence (61), and the polyadenylation signals TACATA (47) and AATAAA (25) are present in the downstream sequence. In addition, the sequence between positions -247 and -230 matches a characteristic heat shock regulatory element containing GAA segments repeated at 2-nucleotide intervals in alternating orientations (1,66).…”
Section: Resultssupporting
confidence: 68%
“…The amino acid composition of the first 53 amino acids in the predicted hsp78 sequence is consistent with the properties of known mitochondrial leader peptides (46). Two TATA boxlike sequences are present at positions -103 and -93 in the 5' upstream sequence (61), and the polyadenylation signals TACATA (47) and AATAAA (25) are present in the downstream sequence. In addition, the sequence between positions -247 and -230 matches a characteristic heat shock regulatory element containing GAA segments repeated at 2-nucleotide intervals in alternating orientations (1,66).…”
Section: Resultssupporting
confidence: 68%
“…The 1,831-bp cDNA for clone CYP28A1 and the 1,764-bp cDNA for clone CYP28A2 contain open reading frames encoding proteins of 506 and 505 residues, respectively. The 3Ј untranslated regions of CYP28A1 and CYP28A2 both contain a putative polyadenylation signal [AATAAT and AATAAA, respectively (27)] within 15 bases of the poly(A) tail.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary structure for the 3ЈUTR of ATM1 and other nuclearly encoded mitochondrial genes predicted several long and stable doublestranded regions. Additionally, for all of them the AU content is approximately 70%, a finding which is reminiscent of the highly conserved 3ЈUTR of nucleus-encoded mitochondrial proteins of rat liver (28). It has been shown that the 3ЈUTR of the ␤1-F1 ATPase transcript is involved in controlling the translation, stability, and subcellular localization of the mRNA during rat liver development (18).…”
Section: Discussionmentioning
confidence: 96%
“…To better characterize the nucleotide sequence within the 3ЈUTR of ATM1 responsible for mRNA transport to mitochondrion-bound polysomes, the regions between the stop codon and the canonical polyadenylation signal sequence AATAAA (28) were shortened by 97 and 238 bp, respectively (Fig. 6B).…”
Section: Fig 3 Expression and Localization Of Gfp-atm1p Chimeras (A)mentioning
confidence: 99%